Literature Review on Microfinance as an Instrument for Empowering The Economy of Low-Income Communities - Sri Wahyuni Israfatin Bobihu; Rianda Hanis; Itsna Rahma Fitriani; Mutia Pamikatsih; Meiyanti Widyaningrum (Economics And Business Management Journal ( EBMJ ), 2025)
Microfinance is a crucial instrument in empowering the economy of low-income communities in Indonesia. This study aims to examine the effectiveness of microfinance in improving economic well-being, the challenges it faces, and the role of financial technology (fintech) in its development. The research employs a literature review method with descriptive analysis of various scholarly sources from 2019 to 2023. The findings indicate that microfinance contributes to increased access to capital, household income growth, financial inclusion, and women's empowerment. However, several challenges remain, including credit risk, low financial literacy, and dependence on external assistance. Fintech has enhanced accessibility and efficiency in microfinance services, yet it still faces regulatory and data security challenges. To enhance the effectiveness of microfinance, strategies such as improving financial literacy, strengthening regulations, diversifying funding sources, and utilizing digital technology are necessary. With the right policies, microfinance can continue to serve as a sustainable instrument for improving the economic well-being of low-income communities in Indonesia.